Prediction of Ovarian Response in Women with Premature Ovarian Insufficiency Stimulated By Gonadotrophins Using Day-3 Serum Estradiol: A Retrospective Study - Teama M (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2016)
Objective: The aim of this study was to evaluate the potential predictive value of day-3 serum estradiol for follicle growth, ovulation, and pregnancy rate in women with premature ovarian insufficiency.  Patients and Methods: This was a retrospective study which was carried out in International Fertility Centre Kingdom Saudi Arabia. The study included 80 consented women with desired fertility who were treated and monitored between the years of 2013-2016 into this study. The clinical, endocrinologic, chromosomal, and immunologic characters of these women were gathered. The main outcome values were follicle growth, ovulation, and pregnancy rate.  Results: In the current study, it was found that women with follicle growth, ovulation, and pregnancy rates were not significantly different as a function of parity, iatrogenic history, age of disease onset, follicle stimulating hormone (FSH) level at the time of diagnosis. The serum E2 levels on days 3 of withdrawal bleeding (Day 3 E2) were significantly higher in the cycles with successful follicle growth and ovulation than unsuccessful cycles (P < 0.05). Receiver-operator characteristic curve (ROC) analysis revealed the cutoff value of the Day 3 E2 to be 25 pg/mL for follicular growth, ovulation and spontaneous pregnancy.  Conclusion: In this study we found that those cycles with a Day 1-5 E2 ≥ 25 pg/mL have a higher rate of follicle growth and ovulation in patients with POI.